Pembelajaran Rangkaian Digital Berbasis Kecerdasan Buatan: Peluang dan Tantangan - Chandra, Francisca Haryanti (SinarFe7, 2025)
The development of Artificial Intelligence (AI) has significantly impacted education, including foundational courses such as Digital Circuits in Electrical Engineering. AI offers substantial opportunities through personalized learning, interactive simulations, and teaching efficiency. However, unmonitored use of AI poses challenges, including students’ dependency on instant answers, declining learning motivation, and degradation of critical thinking skills. This study employs a Systematic Literature Review (SLR) of ten academic articles published between 2019–2024, complemented by reflections from teaching experience before and after the mid-term examination. The findings reveal that AI integration must be proportional. Prior to the mid-term, students tended to engage in covert use of AI, while after the mid-term, the adoption of a guided use model, combined with group assignments, improved both conceptual understanding and social interaction. These findings led to the formulation of the AI–Humanistic learning model, which integrates AI with humanistic values such as critical thinking, collaboration, and social relationships. This study is limited to a single course, Digital Circuits, and thus further research is needed to validate the AI–Humanistic model across different courses and involving more instructors to provide a more comprehensive perspective.